Impact of COVID-19 on People with Disabilities in Nepal: A Preview into Assistive Technology Use during Pandemic - Mathema, Sujala; Aryal, Bhagwan; Subedi, Sibila (Nepal Journal of Multidisciplinary Research, 2023)
This article is related to a desk study on the impact of COVID-19 on the lives of people with disabilities and the use of assistive technology together with the impact of assistive technology use by people with disabilities during the pandemic in Nepal. Along with the impact on the global economy, food security, and mental health, COVID-19 has devastating effects on the healthcare systems, shifting resources from disease treatments to the management of COVID-19. In such crises, marginalized groups such as people with disabilities are often neglected. An intensive literature search was performed in PubMed and Google Scholar with a thorough search of all possible government and non-government reports on the research interests. The situation was found to be devastating in a low-income country like Nepal where the majority of the people with disabilities were not provided with government social protection assistance. People with disabilities experienced an increased level of anxiety and depression because of the pandemic and lockdowns in the country. Many people with disabilities heavily depend on assistive technology to perform their daily activities but due to the pandemic delivery of assistive technology services has reduced drastically. A disability-inclusive response is recommended to empower people with disabilities to handle their lives in difficult circumstances, and increase access to health care, and assistive technology use.